2011
DOI: 10.1017/jfm.2011.304
|View full text |Cite
|
Sign up to set email alerts
|

A falling film down a slippery inclined plane

Abstract: A gravity-driven film flow on a slippery inclined plane is considered within the framework of long-wave and boundary layer approximations. Two coupled depth-averaged equations are derived in terms of the local flow rate $q(x, t)$ and the film thickness $h(x, t)$. Linear stability analysis of the averaged equations shows good agreement with the Orr–Sommerfeld analysis. The effect of a slip at the wall on the primary instability has been found to be non-trivial. Close to the instability onset, the effect is dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 42 publications
8
46
1
Order By: Relevance
“…Computed velocity profiles with backflow are depicted in figure 7 of [13], with potential inflexion points which could indicate that a cubic profile may be a more suitable approximation in this region. This is in agreement with work by Samanta et al [20], who conclude that in a nonlinear regime, the backflow phenomenon is shown to be intensified by a no-slip condition enforced between the fluid and the plane. Backflow in the capillary region is investigated experimentally by Dietze et al [7].…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Computed velocity profiles with backflow are depicted in figure 7 of [13], with potential inflexion points which could indicate that a cubic profile may be a more suitable approximation in this region. This is in agreement with work by Samanta et al [20], who conclude that in a nonlinear regime, the backflow phenomenon is shown to be intensified by a no-slip condition enforced between the fluid and the plane. Backflow in the capillary region is investigated experimentally by Dietze et al [7].…”
Section: Introductionsupporting
confidence: 93%
“…Often used for describing falling films, the long wave equation, and other similar models, are derived using a perturbation expansion method for the stream function, determined to O("), and then substituted into the surface kinematic boundary condition. An early publication using this method by Benney [2] gives a single evolution equation for film thickness, however this has been criticised as predicting unrealistic wave profiles as the wave amplitude increases [14], as well as leading to finite-time singularities [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This originates from the inclusion of the curvature term 2 S zz in Eq. (24). Being similar to the exterior case, the cutoff wave number corresponds to the classical Rayleigh-Plateau mode for the capillary instability of a viscous jet.…”
Section: A Temporal Stability Analysismentioning
confidence: 92%
“…The one-sided model has been widely used in many recent papers on the stability of falling films on porous inclines [21][22][23]. In mathematical form, this one-sided model is identical to that of the problem of a film falling down a slippery inclined plane [24]. Liu and Liu [25] proposed a two-sided model by giving up the assumptions in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth mentioning here that flow over rough or textured substrates at the microscale and/or superhydrophobic substrates can be examined by modelling these substrates as smooth substrates with an effective slip at the interface [33]. Further, Blake [34], Vinogradova [35,36], and Voronov and Papavassiliou [37] have pointed out that large slip lengths of the order of 50 µm can be observed in the case of grooved substrates when one considers the combination of the above two effects, and therefore, flow over grooved substrates can be again analysed using flow over a slippery substrate.…”
Section: Introductionmentioning
confidence: 99%